Triacetonitrile(1,4,7-trimethyl-1,4,7-triazacyclononane)cobalt(II) bis(tetraphenylborate) - Jeongcheol Shin; Jin Kim; Jonghoon Choi (IUCrData, 2024)
The title cobalt(II) complex, [Co(C2H3N)3(C9H21N3)](C24H20B)2 or [(tacn)Co(NCMe)3][BPh4]2, has been characterized by single-crystal X-ray diffraction. It incorporates the well-known macrocyclic tacn (1,4,7-trimethyl-1,4,7-triazacyclononane) ligand, which is coordinated facially to the metal center. The complex crystallizes in space group P21/c with Z = 4. The divalent cobalt ion exhibits a six-coordinate octahedral geometry by one tacn and three acetonitrile ligands. Two non-coordinating tetraphenylborate (BPh4−) anions are also present.